Effects of Motor-Games-Based Concurrent Training Program on Body Composition Indicators of Chilean Adults with Down Syndrome - Cofre-Bolados, C; De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Background: Concurrent training of strength and endurance has been widely ued in the field of health, with favorable effects on body composition. However, the effect on the body composition of a ludic-motor concurrent proposal in adults with Down syndrome has not been quantified yet. The aim of this study was to determine the effect of a concurrent training program based on motor games on body composition indicators and cardiometabolic risk on schooled male adults with Down syndrome. Methods: The sample is composed of 15 male adults with Down syndrome from Chile. Body composition variables such as body mass index, waist circumference, height to waist ratio, skin folds, perimeters, and muscle areas were assessed at the beginning and end of the program. Subsequently, a program of motor games was designed and implemented for 10 months. Results: Mean and standard deviation for body fat were pre (25.36 ± 5.60) and post (23.01 ± 6.20)%; waist circumference pre (86.00 ± 8.97) and post (82.07 ± 8.38) cm. Brachial perimeter and muscle area were pre (22.30 ± 2.80) and post (23.61 ± 2.28) cm; pre (40.19 ± 10.09) and post (44.77 ± 8.48) cm2, respectively. Our findings showed significant results (p < 0.05): body fat %; sum of folds; waist circumference; height to waist ratio; brachial perimeter and brachial muscle area. Conclusion: A concurrent training program implemented through motor skills games decreases body fat and cardiovascular risk and increases the muscle mass in male adults with Down syndrome. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.